FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KECELAKAAN KERJA DI DIVISI PRODUKSI SPINNING UNIT 2 PT X KARANGANYAR - Wartini (Universitas Veteran Bangun Nusantara, 2024)
Based on a preliminary survey on work accident report data for 3 years. In 2019 there were 21 work accident cases, in 2020 there were 40 work accident cases, and in 2021 there were 23 work accidents. The purpose of this study was to determine the relationship between the variables age, gender, years of service, unsafe behavior, unsafe conditions with work accidents at PT Adikencana Mahkotabuana Karanganyar. This type of quantitative research with a cross sectional approach. The research was conducted from December 2022 to January 2023. The population was PT X spinning unit 2 production workers, the sample was 186 workers. The sampling technique uses Quota Sampling. The research instrument used a questionnaire about factors related to work accidents. Methods of data analysis using the Chi-square test. The results of this study show that the variables associated with the occurrence of work accidents are years of service (p=0.006), unsafe behavior (p=0.001), and unsafe conditions (p=0.000).. Based on the results of this study, it is suggested to improve the quality of new workers by providing knowledge and importance related to SOPs and rules, increasing the role of supervisors' strictness and discipline, imposing rewards and punishments, increasing housekeeping to keep floors clean from scattered cotton waste, and providing knowledge and rules on the importance of using shoes with non-slip soles.